Alginate extraction from Sargassum seaweed in the Caribbean region: Optimization using response surface methodology. (1st October 2020) - Mohammed, Akeem; Rivers, Arianne; Stuckey, David. C.; Ward, Keeran
Graphical abstract: Highlights: Box-Behnken Design coupled with multistage extraction used to optimize alginate extraction. Temperature and time amongst conditions significantly affecting extraction yield. Purified alginate extracts gave yields of 21 % with a purity of 92 %. Alginate characterization gave an M/G ratio of 0.45. Extracted alginates useful in producing strong gels. Abstract: Sargassum valorization has become increasingly important as the Caribbean region continues to struggle with the massive growth of the seaweed and its damaging effects. Sodium alginate extraction is one method where the seaweed biomass can be utilized to produce a useful biopolymer. However, current processing generally giving low yields of inferior quality, making it unattractive for commercialization. This article seeks to optimize the extraction process using a Box-Behnken Response Surface Design combined with multistage extraction to obtain higher product yield and purity, as well as giving insights, for the first time, into the physiochemical properties of the extracted alginate from Sargassum biomass. Optimum conditions were found and confirmed through validation, with a crude yield as high as 28 % after 2 stages and a purity of 92 % for purified alginate samples. Characterization of the bleached alginate through NMR studies validated with FTIR, gave an M/G ratio of 0.45 with a molecular weight of 3.14 × 10 5 g mol −1 and viscosity of 14.10 cP aligned to high gelling capabilities.